2017
DOI: 10.1007/978-3-319-60189-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury-Induced Neurotoxicity: Focus on Pro-oxidative Events and Related Consequences

Abstract: Methylmercury (MeHg) is a highly neurotoxic environmental pollutant. Even though molecular mechanisms mediating MeHg toxicity are not completely understood, several lines of evidence indicate that the neurotoxic effects resultant from MeHg exposure represent a consequence of its pro-oxidative properties. In this regard, MeHg is a soft electrophile that preferentially interacts with (and oxidize) nucleophilic groups (mainly thiols and selenols) from biomolecules, including proteins and low-molecular-weight mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 100 publications
4
23
0
Order By: Relevance
“…Mitochondria are implicated in a number of neurodegenerative diseases and iHg localises to mitochondria (Chang and Hartmann 1972 ). Mercury has a particular affinity for the sulfhydryl groups of cysteine-containing proteins (Clarkson and Magos 2006 ) found in lipid membranes of the Golgi apparatus, the endoplasmic reticulum and lysosomes, all of which have been linked to neurodegenerative diseases (Farina and Aschner 2017 ). Furthermore, ultrastructural studies have shown iHg binds to all these lipid-rich sites in the nervous system (Chang and Hartmann 1972 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are implicated in a number of neurodegenerative diseases and iHg localises to mitochondria (Chang and Hartmann 1972 ). Mercury has a particular affinity for the sulfhydryl groups of cysteine-containing proteins (Clarkson and Magos 2006 ) found in lipid membranes of the Golgi apparatus, the endoplasmic reticulum and lysosomes, all of which have been linked to neurodegenerative diseases (Farina and Aschner 2017 ). Furthermore, ultrastructural studies have shown iHg binds to all these lipid-rich sites in the nervous system (Chang and Hartmann 1972 ).…”
Section: Discussionmentioning
confidence: 99%
“…Methylmercury (MeHg) is a global environmental contaminant targeting the central nervous system (CNS) (Farina and Aschner 2017;Santos et al 2016). Consumption of MeHg-containing fish products (Canuel et al 2006;Carrasco et al 2011;Steuerwald et al 2000;Stopford and Goldwater 1975) and rice (Rothenberg et al 2014;Zhang et al 2010) has been shown to induce neurodegeneration as well as be associated with neurodevelopmental disorders (Belletti et al 2002;Carocci et al 2014;Ceccatelli et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…MeHg is one of the environmental accumulative pollutants that could easily pass through the bloodā€brain barrier and accumulate in the brain especially in the CNS . The mechanisms of MeHg neurotoxicity have not been fully elucidated, in which oxidative stress and Gluā€mediated excitotoxicity involved may play important roles …”
Section: Discussionmentioning
confidence: 99%